2022
DOI: 10.3389/fcvm.2022.949778
|View full text |Cite
|
Sign up to set email alerts
|

Decreased low-density lipoprotein receptor-related protein 1 expression in pro-inflammatory monocytes is associated with subclinical atherosclerosis

Abstract: Subclinical atherosclerosis (SCA) occurs in asymptomatic individuals. Blood peripheral monocytes are involved in the development of atherosclerosis. Circulating monocytes acquire pro-inflammatory profiles, and they are involved in the early stages of atherosclerosis development. Low-density lipoprotein Receptor-related Protein 1 (LRP1) is expressed in monocytes, mainly in classical and intermediate subsets. Although LRP1 is highly expressed in macrophages and vascular smooth muscle cells (VSMCs) in atheroscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…In this context, it has recently been shown that the impact of CCR2 + monocyte subpopulations even reveals sexual dimorphism, where boys seem to be at higher atherosclerosis risk than girls ( 32 ). Further, it has been suggested that proinflammatory circulating monocytes are particularly involved in the early stages of atherosclerosis development ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has recently been shown that the impact of CCR2 + monocyte subpopulations even reveals sexual dimorphism, where boys seem to be at higher atherosclerosis risk than girls ( 32 ). Further, it has been suggested that proinflammatory circulating monocytes are particularly involved in the early stages of atherosclerosis development ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is another disease in which peripheral blood monocytes are involved. Circulating monocytes with pro-inflammatory profiles are known to be implicated in the early stages of atherosclerosis development ( 67 ). It has been shown that LRP1 is also engaged in atherosclerosis development, specifically in atherogenic plaque formation ( 6 ).…”
Section: In Monocytesmentioning
confidence: 99%
“…It has been shown that LRP1 is also engaged in atherosclerosis development, specifically in atherogenic plaque formation ( 6 ). It has been proposed that decreased LRP1 expression in pro-inflammatory monocytes is linked with development of atherosclerosis ( 67 ).…”
Section: In Monocytesmentioning
confidence: 99%